Die Vegetationszonen Nord-Eurasiens während der postglazialen Wärmezeit - Frenzel, Burkhard (ERDKUNDE, 1955)
This review article, mainly based on Russian literature, gives a summary of the present state of knowledge of the zoning of vegetation during the Post-glacial Warm Period. The data mentioned in these publications refer to the early and middle stages of this period without, however, stating exactly for each individual case to whidi part of the period it belongs. It was nevertheless possible to reconstruct the following picture of the vegetation zones in northern Eurasia during the Post-glacial Warm Period. The tundra proper had then disappeared almost completely and was restricted only to small areas on the Yamal, Gyda and Taimyr peninsulas. The forest tundra which, with the exception of the section east of the Taimyr peninsula to eastern Siberia where it was virtually eliminated from the continent by the taiga, extended everywhere to the Arctic Ocean, and consisted to a much greater degree than today of birdies, supplemented in the western section by pines and in the eastern section by larches. Though the taiga had expanded to the north most markedly, its southern margin also lay further north than today. The forest zone in European Russia was characterized by mixed oak forests, with a considerable admixture of pines; east of the Urals, as today, pure stands of coniferous forests consisting of many species prevailed, but extended further eastward than at present. In the European part of the U.S.S.R. the steppe and the forest-steppe advanced at many points into the taiga, but this was more pronounced in Middle Siberia where loess-steppes accompanied the middle and upper course of the Lena river and thus formed a transitional zone leading to the steppe regions round Lake Baikal. Nevertheless they were in all cases localized steppes which were not in direct contact with the great steppe zone of Middle and Central Asia. During the Post-glacial Warm Period this region and vegetation zone occupied a much larger area than today. For instance, loess-steppes reached a height of 1000 m. on the flanks of the mountains of Middle Asia and it was then that the desert land forms, which today are largely of a fossil kind, originated in the dry areas of Middle Asia, and the lakes considerably decreased in size. Some extended over a smaller area than today (e. g. the Caspian Sea), while others were intermediate between the size they had assumed during the last Glacial period and that which they occupy at present (e. g. Lake Balkash, Saisan-nor). Together with the northward expansion of the polar limit of the steppe zone went an upward expansion of the upper altitudinal limit, so that Tibet was covered by a luxuriant herbaceous steppe.